(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Licorice root and its primary active component, glycyrrhizic acid, have long been studied for their therapeutic properties, including anti-inflammatory, antiviral, and hepatoprotective effects. This research investigates the effects of licorice root extract on the immune system, with a specific focus on its impact following radiation-induced secondary immunodeficiency. The study utilizes 25 male white red-eyed rats, which were exposed to light therapy using the Terabalt apparatus to induce immunodeficiency. Rats were divided into five groups, with varying treatments of glycyrrhizic acid solutions (0.01% and 0.03%) and Polyoxidonium, while a control group received no radiation. Antibody-producing cells, erythrocytes, and leukocytes were assessed post-treatment. Results indicated that glycyrrhizic acid significantly influenced the proliferation of T- and B-lymphocytes, highlighting its potential as a biostimulant to enhance immune function. These findings suggest that licorice root extract can play a crucial role in mitigating the adverse effects of radiation therapy and promoting immune recovery.